2019
DOI: 10.1186/s41240-019-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adductor muscle growth by the IGF-1/AKT pathway in the triploid Pacific oyster, Crassostrea gigas

Abstract: We investigated the insulin-like growth factor 1 (IGF-1)/AKT signaling pathway involved in muscle formation, growth, and movement in the adductor muscle of triploid Pacific oyster, Crassostrea gigas. Large and small triploid oysters (LTs and STs) cultured under identical conditions were screened, and the signaling pathways of individuals with superior growth were compared and analyzed. mRNA and protein expression levels of actin, troponin, tropomyosin, and myosin, proteins important in muscle formation, were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have also related TRPCs to PI3K-AKT signaling pathways [ 35 ]. AKT was reported increased expression under hypoxia conditions in the smooth muscle of C. gigas , involving in metabolism of muscle protein [ 36 , 37 ]. In terms of that, the inducible expression of TRPC3.6 in adductor muscle as we observed in this work may indicate its functional role in energy regulation in response to heat stress and oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also related TRPCs to PI3K-AKT signaling pathways [ 35 ]. AKT was reported increased expression under hypoxia conditions in the smooth muscle of C. gigas , involving in metabolism of muscle protein [ 36 , 37 ]. In terms of that, the inducible expression of TRPC3.6 in adductor muscle as we observed in this work may indicate its functional role in energy regulation in response to heat stress and oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PI3K leads to the production of PIP3, which in turn promotes the activation of downstream factors such as AKT, TOR, and GSK3β to regulate cell proliferation, energy metabolism, and hormone secretion [ 49 ]. Recent studies have reported the involvement of several major members of the PI3K-AKT and RAS-MAPK signaling pathways in the regulation of adductor muscle growth in the triploid Pacific oyster [ 31 , 32 ]. In our present study, based on gene expression profiles, we found that the ILPR-mediated signaling pathway was conserved among vertebrates and invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genes involved in the PI3K-AKT and RAS-MAPK signaling pathways, such as PI3K, AKT, PTEN, and RAS, were also identified in invertebrates [ 28 , 29 , 30 ]. Levels of expression or phosphorylation of key components of these pathways have been associated with growth difference [ 29 , 31 , 32 , 33 , 34 , 35 ]. A recent study on pearl oysters reported that the insulin-like peptide recombinant protein induced the expression of ILPR and the major genes of the PI3K-AKT and RAS-MAPK pathways, suggesting a functional IIS signaling cascade mediated by ILPR [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, Thompson et al [ 65 , 66 ] found that proteins associated with cytoskeleton activity (actin, actin-2, tropomyosin, and myosin) were affected in Saccostrea glomerata by exposure to copper (Cu) and lead (Pb), and with the latter, tropomyosin concentration increased fourfold, affecting motility and cellular plasticity of hemocytes. Troponin C, the calcium receptor subunit [ 67 ], is still unclear in mollusks; some studies on TnC have been performed on Patinopecten yessoensis [ 68 , 69 ], Ruditapes philippinarum [ 70 ], and C. gigas [ 71 ], associating it with physiological functions, mainly in muscle tissues as an important part in muscle formation and contraction. However, studies carried out by Funabara et al [ 72 , 73 ] in Pinctada fucata indicate that TnC genes are mainly expressed in adductor phasic muscles and rarely in adductor catch muscles, gills, mantles, and feet.…”
Section: Discussionmentioning
confidence: 99%